2020
DOI: 10.18226/21789061.v12i1p43
|View full text |Cite
|
Sign up to set email alerts
|

Internal Assessment of the Tourist Offer Development Level Based on its Resources, Attractions and Tourist Products

Abstract: Este estudo avalia o grau de desenvolvimento da oferta turística [OT], segundo a percepção dos principais stakeholders do próprio destino turístico [DT]. A lente teórica sobre gestão de destinos, focalizada na gestão de operações e processos, enquadrou a discussão sobre os conceitos de 'recursos' [RT], 'atrativos' [AT] e 'produtos turísticos' [PT], e o processo de conversão de RT em AT e PT. Metodologicamente, o estudo realizado em Juiz de Fora-MG [Brasil] dividiu-se em três fases: (1) survey, com dados secund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The tourist attractions of Juiz de Fora were mapped in a previous study (Pimentel, 2019;Pimentel and Carvalho, 2020), and of the set of 110 items identified, of which 35 were directly analyzed, classified, evaluated and hierarchized in previous study (Pimentel and Carvalho, 2020), 15 of them (from this set of 35) were directly related to the current research.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The tourist attractions of Juiz de Fora were mapped in a previous study (Pimentel, 2019;Pimentel and Carvalho, 2020), and of the set of 110 items identified, of which 35 were directly analyzed, classified, evaluated and hierarchized in previous study (Pimentel and Carvalho, 2020), 15 of them (from this set of 35) were directly related to the current research.…”
Section: Methodsmentioning
confidence: 99%
“…Tourist attractions are, under any angle, the fundamental raw material in the composition of any tourist activity or system (Domingues, 1994;Veloso, 2003;Carvajal-Zambrano & Lemoine-Quintero, 2018;Pimentel & Carvalho, 2020), since they constitute a critical success factor for tourism. This is because ultimately the tourist attraction is the driving force behind all activity.…”
Section: Tourist Attractionsmentioning
confidence: 99%
See 3 more Smart Citations